(untitled) (Malaysian Journal of Civil Engineering, 2018)
In the field of nanotechnology, Carbon nanotube (CNT) has the prime focus as one of the most important areas of research. A major difficulty of producing CNT-cement composites is the attainment of uniform dispersion of CNT. CNT has a tendency to agglomerate creating zones of weakness in composite materials. In this study, a parametric study was carried on surface treated multiwalled carbon nanotubes (MWNT) reinforced cementitious composites having different mix proportions and an attempt was made to establish a relation between compressive strengths and flow values of composites samples. It was observed that the effect of flow values on compressive strength was most pronounced at 28 day. Composites made with surfactant exhibited less fluctuation in flow values and corresponding compressive strengths. A higher flow value of MWNT added composites, having same mix proportion, represents more uniform distribution of MWNT within the cement grains and more stable mix. Furthermore, less variation in flow values represents more stable dispersion technique to distribute CNT within cement matrix.